Students Language Performance and TOEFL Preparation Program, Are they connected? - Malik, Ermansyah; Ai-Chun, Yen; Te-Sheng, Chang (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study examines and describes the relationship between TOEFL preparation Program and Students; language performance. The study also examines the program's effect on students' TOEFL scores improvement. Using spss v.22 in analyzing the data, the researcher employed three groups of students consisting of 15 students, namely the control group, treatment 1 group, and the treatment two groups. Thus, descriptive statistics present verifiable data in numerical form, which uses statistical procedures to tabulate, describe, reflect, and summarize data properties. The two variables data examined, TOEFL paper-based testing score and FCE Cambridge speaking test score, are the focus of the research, free from context generalization of the phenomenon. The result is presented statistically using quantitative methodology. The control group was not exposed to any treatment, while 1 group was given basic general English lessons, and the treatment 2 group was trained using the specially designed TOEFL preparation course. The study result shows significant effects on the improvement of TOEFL score on the treatment 1 group's pre-test mean, the standard of deviation, and the standard error mean were 350.07, 22.745, and 5.873, respectively. The treatment 2 group's mean, the standard of deviation, and the standard error mean were 355.40, 20.117, and 5.194, respectively, and the treatment 1 group' post-test mean, the standard of deviation, and the standard error mean were 387.27, 35.204, and 9.090, respectively. The treatment 2 group's mean, standard of deviation, and standard error mean were 436.87, 44.912, and 6.925, respectively. However, the study result shows that the correlation p-value = .083 indicates no significant correlation between TOEFL Preparation students' language performance.